Penerapan Data Mining Untuk Mengetahui Minat Siswa Pada Pelajaran IPA Mengunakan Metode K-Means Clustering - Mardiansa Mardiansa; Herlina Latipa Sari; Prahasti Prahasti (Jurnal Multidisiplin Dehasen (MUDE), 2023)
The purpose of this research is to build a data mining application to find out students' interest in science subjects at SMPN 18 Bengkulu City. With data collection techniques by way of observation and interviews, this study used a sample of data on grades IX.8 science subjects with a total of 30 students at SMPN 18 Bengkulu City. The research method used is the K-Means Clustering method because this method separates data into groups that have objects with similar characteristics. In building this application using Xampp server, PHP programming language and MySQL database. This datamining application is used to make it easier for a teacher or admin in this application to manage student data to determine student interest in science subjects. The results of this study were 3 groups of students' interest in science subjects, namely 12 students with high interest, 17 students with moderate interest and 1 student with low interest in SMPN 18 Bengkulu City.